Biometric Fingerprint Liveness Detection - Váňa, T. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
This paper deals with biometric fingerprint liveness detection. A software-based liveness detection approach using neural network is proposed. To distinguish between live and fake samples, three image quality features extracted from one image are used. The algorithm is tested on LivDet database comprising real and fake images acquired with three sensors.
Keywords: Biometric system; fingerprint; liveness detection; LivDet database; neural network